2006
DOI: 10.1007/s10518-006-9026-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of strong ground motion data recorded in the Gubbio sedimentary basin (Central Italy)

Abstract: Various authors, analysing the set of accelerograms recorded at Gubbio Piana (GBP) (central Italy), have demonstrated that strong amplification occurs at this accelerometric station, which is installed within an alluvial basin. In particular, Ambraseys et al. [(2005a), Bull Earthq Eng 3:1-53; (2005b), Bull Earth Eng 3:55-73] observed that the strong motion peaks at GBP greatly exceed the median values predicted by the attenuation relationships they derived for Europe. In this work, we analyse and discuss some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…5-Preparation of representative geotechnical profiles of the city based on the geological, sedimentological, geotechnical, geophysical and geoelectrical data; 6-Estimation of strong ground motion characteristics using one-dimensional site response analysis of the representative geotechnical profiles; 7-Preparation of the surface and sub-surface grain size maps of the study area in the Geography Information System (GIS) media and geological cross sections in various directions.8-Preparation of the final site periods and peak ground acceleration (PGA) maps of each area in GIS. [10]. b) Major and minor active faults in Iran [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-Preparation of representative geotechnical profiles of the city based on the geological, sedimentological, geotechnical, geophysical and geoelectrical data; 6-Estimation of strong ground motion characteristics using one-dimensional site response analysis of the representative geotechnical profiles; 7-Preparation of the surface and sub-surface grain size maps of the study area in the Geography Information System (GIS) media and geological cross sections in various directions.8-Preparation of the final site periods and peak ground acceleration (PGA) maps of each area in GIS. [10]. b) Major and minor active faults in Iran [7].…”
Section: Methodsmentioning
confidence: 99%
“…There are several ways of assessing site effects. The characterization of a given site can be achieved based on Instrumental or theoretical-analytical or numericalapproaches to the problem [8,9,10]. In order to classify the regions of the city in terms of site stability for building reconstructions for future urban planning, I performed several investigation case studies on soil and subsurface sediments in 5 cities of Iran and here I want to introduce some results of them in this paper.…”
Section: Isbn 978-93-84468-11-8 Proceedings Of International Conferenmentioning
confidence: 99%
“…The area has been selected because the urban and geomorphologic characteristics of the town of Gubbio and its surrounding are representative of many areas in Central Italy, that is a valuable historical centre founded on a rocky hillside with new residential and industrial areas developed on an alluvial plain. A great deal of effort has been put into the seismic characterisation of the Gubbio basin, also called the Eugubina plain [1]; [2], since recent studies (e.g. [1]), based on the analysis of available strong motion data, have shown that significant site amplification takes place, with the main contribution due to surface waves.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of effort has been put into the seismic characterisation of the Gubbio basin, also called the Eugubina plain [1]; [2], since recent studies (e.g. [1]), based on the analysis of available strong motion data, have shown that significant site amplification takes place, with the main contribution due to surface waves. In particular, the strong motions recorded at the accelerometric station GBP, belonging to the RAN (Rete accelerometrica italiana), installed within the alluvial basin, shows strong amplification and lengthening of significant ground-shaking duration compared to rock sites.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], we extended the method of [61] to the wavelet domain in order to use the instantaneous attributes for filtering and wavefield separation for any number of components. As an example, reference [63], used this method for spectral analysis and multicomponent polarization analyses on the Gubbio Piana (central Italy) recordings to identify the frequency content of the different phases composing the recorded wavefield and to highlight the importance of basin-induced surface waves in modifying the main strong ground-motion parameters.…”
Section: Polarization Properties For Three-component Datamentioning
confidence: 99%